Stan kliniczny dziecka przedwcześnie urodzonego a rozwój 3. stadium retinopatii wcześniaków - Niwald, Anna; Krajewski, Paweł; Orawiec, Beata; Piotrowski, Andrzej; Grałek, Mirosława (Klinika Oczna / Acta Ophthalmologica Polonica, 2005)
The aim of the study was to determine the prognostic value of some pathologies related to prematurity in the development of stage 3 ROP in children with extremely low birth-weight. The group of 35 prematures with diagnosed 3rd stage ROP and 64 prematures without ROP was examined. The presence of the respiratory distress syndrome (RDS), persistent ductus arteriosus (PDA), necrotizing enterocolitis (NEC) and intraventricular haemorrhages (IVH) were analyzed. RDS was more frequent in prematures with 3rd stage ROP (p=0.005, OR=3.59). There was significant difference between the frequency of IVH in both groups (p = 0.03), but the odds ratio was significantly high only in the children with the 3rd stage IVH (OR=2.42). PDA was diagnosed more frequently in children with 3rd stage ROP but the difference was not statistically significant (p=0.152, OR=1.80). There was significant difference between the groups when comparing the incidence of NEC (p=0.03, OR=3.34). The pathologies of the prematurity such as RDS, NEC and grade III IVH are the predictive factors for the development of stage 3 ROP (p=0.03, OR=3.34).